Dismantling Hegemonic Masculinity: An (auto)Ethnography of Varones por el Cambio - Piñeyro Nelson, Carlos (2022)
Based on digital ethnography and autoethnography, this essay will discuss the deconstruction experience of «Varones por el Cambio», an over 40 years-old male heterosexual group created in 2020 in Mexico. Its members only interact using social networks such as WhatsApp and virtual conference apps. Using Luis Bonino’s theory on Micromachismos, this organization has questioned basic patterns of hegemonic masculinity, such as men’s violence toward women, female cosification, and the need to talk about men’s «denied» feelings (fear, frustration, love). By showing Varones por el Cambio’s experience, I pretend to discuss the possibilities and the limits of male groups seeking to deconstruct aspects of hegemonic masculinity using only social media.